Assessment of dimethoate in olive oil samples using a dual responsive molecularly imprinting-based approach - Garcia, Raquel (2020)
FCT-Foundation for Science and Technology under the Project UIDB/05183/2020. Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES (UIDB/50006/2020).